Analysis of Slope Instability Processes Through Comparison of Limit Equilibrium and Finite Element Methods - Leguizamón Barreto, Luis Carlos; Ménendez Tellez , Juan José (Ingeniería Solidaria, 2020)
Introduction: The article presents research results on the analysis of slope instability processes, conducted at the Universidad Pedagógica y Tecnológica de Colombia in 2019.Problem: Slope instability processes are permanently present in the state of Boyacá – Colombia. The stability analysis through the application of conventional limit equilibrium methods does not reflect the real conditions of mechanical resistance of the materials found.Aim: Analyze slope instability processes utilizing the finite element method in two critical spots located on the road that connects the city of Tunja with the town of Miraflores.Methods: Start with the search and compilation of information from critical spots with relevant geotechnical characterization on roads in the state, thereby permitting the identification of two unstable critical spots. With the use of geological, geotechnical and hydrological information, the mechanical behavior of the materials is modelled through the software Slide and Midas GTS NX.Results: The estimation of material stability through the finite element method shows more reliable results compared to the actual behavior of the studied locations and compared to the methods based on limit equilibrium.Conclusion:The use of this numerical simulation technique is recommended to replace conventional methods, being an affordable and effective tool for the analysis of instability processes.Originality: Most analyses of instability processes conducted in the state of Boyacá – Colombiado not use the finite element method.Limitations: The estimation of material stability is based on a constitutive model for soil and another for rock.
Keywords: material instability; slope stability; limit equilibrium; finite elements